2016
DOI: 10.1002/chem.201605146
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Self‐Recognition between Stereogenic Tetrapalladium Units Affording Pd8 Chains Supported by Homochiral Tetraphosphines

Abstract: By using a chiral tetraphosphine, rac-bis[(diphenylphosphinomethyl)phenylphosphino]methane (rac-dpmppm), linear octapalladium chains were synthesized as discrete molecules of [Pd (μ-rac-dpmppm) L ](BF ) (L=CH CN, dmf, XylNC), [Pd (μ-rac-dpmppm) ](BF ) , and [Pd (μ-rac-dpmppm) (Cl) ](BF ) , which are stable in the solution states and characterized by spectroscopic and crystallographic methods to reveal the octapalladium chains supported by homochiral four tetraphosphines. Variable-temperature NMR studies for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The Pt 3 and Pt 2 Pd trinuclear chains with two dpmp ligands, [Pt 2 M(μ‐dpmp) 2 (RNC) 2 ] 2+ (M=Pt, Pd) were reduced to be coupled into the hydride bridged hexanuclear complexes, [Pt 2 M 2 Pt 2 (μ‐H)(μ‐dpmp) 2 (RNC) 2 ] 3+ , which were oxidized by 2 e − to afford the Pt 2 M 2 Pt 2 chains of [Pt 2 M 2 Pt 2 (μ‐dpmp) 2 (RNC) 2 ] 4+ . The tetraphosphines, meso and rac ‐dpmppm have recently proven to stabilize low‐valent octapalladium chains, [Pd 8 (μ‐ meso‐ or rac ‐dpmppm) 4 L 2 ] 4+ (L=none, acetonitrile, N , N ‐dimethylformamide, isocyanides) . Variable temperature NMR studies demonstrated that at higher temperature ( T >100 °C) the Pd 8 chain dissociated into two Pd 4 fragments of [Pd 4 (μ‐ meso‐ or rac ‐dpmppm) 2 L 2 ] 2+ and they were thermodynamically self‐aligned to restore the Pd 8 chain at lower temperature ( T <60 °C).…”
Section: Methodsmentioning
confidence: 99%
“…The Pt 3 and Pt 2 Pd trinuclear chains with two dpmp ligands, [Pt 2 M(μ‐dpmp) 2 (RNC) 2 ] 2+ (M=Pt, Pd) were reduced to be coupled into the hydride bridged hexanuclear complexes, [Pt 2 M 2 Pt 2 (μ‐H)(μ‐dpmp) 2 (RNC) 2 ] 3+ , which were oxidized by 2 e − to afford the Pt 2 M 2 Pt 2 chains of [Pt 2 M 2 Pt 2 (μ‐dpmp) 2 (RNC) 2 ] 4+ . The tetraphosphines, meso and rac ‐dpmppm have recently proven to stabilize low‐valent octapalladium chains, [Pd 8 (μ‐ meso‐ or rac ‐dpmppm) 4 L 2 ] 4+ (L=none, acetonitrile, N , N ‐dimethylformamide, isocyanides) . Variable temperature NMR studies demonstrated that at higher temperature ( T >100 °C) the Pd 8 chain dissociated into two Pd 4 fragments of [Pd 4 (μ‐ meso‐ or rac ‐dpmppm) 2 L 2 ] 2+ and they were thermodynamically self‐aligned to restore the Pd 8 chain at lower temperature ( T <60 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Multinuclear transition‐metal complexes have extensively been studied to explore new aspects of functional materials because a variety of synergistic effects in multimetallic centers are expected to play key roles in developing catalytic systems, electronic, optical, and magnetic devices, and biomimetic functional molecules . To create desired multinuclear centers, design of multidentate metal supporting ligands is very important issue, and in this regard, we have prepared a methylene‐bridged linear tetraphosphane, meso ‐ and rac ‐bis[(diphenylphosphinomethyl)phenylphosphino]methane (dpmppm), and demonstrated that it effectively stabilized versatile tetra‐, tri‐, and dinuclear homo and heterometallic systems as well as mononuclear centers (Scheme ) . First of all, meso ‐ and rac ‐dpmppm preferably supported linearly ordered tetranuclear metal centers in κ 1 ,κ 1 ,κ 1 ,κ 1 coordination mode (Scheme a, Scheme f), exemplified by the linear octapalladium rigid‐rods, [Pd 8 ( meso ‐ or rac ‐dpmppm) 4 L 2 ] 4+ (L = none, MeCN, N , N ‐dimethylformamide (dmf), and isocyanides),, which dissociate at higher temperature T > 100 °C into two tetrapalladium units of {Pd 4 ( meso ‐ or rac ‐dpmppm) 2 } 2+ and interestingly they are self‐aligned at lower temperature T < 60 °C to restore the original rods through asymmetric recognition between the tetrapalladium units .…”
Section: Introductionmentioning
confidence: 99%
“…To create desired multinuclear centers, design of multidentate metal supporting ligands is very important issue, and in this regard, we have prepared a methylene‐bridged linear tetraphosphane, meso ‐ and rac ‐bis[(diphenylphosphinomethyl)phenylphosphino]methane (dpmppm), and demonstrated that it effectively stabilized versatile tetra‐, tri‐, and dinuclear homo and heterometallic systems as well as mononuclear centers (Scheme ) . First of all, meso ‐ and rac ‐dpmppm preferably supported linearly ordered tetranuclear metal centers in κ 1 ,κ 1 ,κ 1 ,κ 1 coordination mode (Scheme a, Scheme f), exemplified by the linear octapalladium rigid‐rods, [Pd 8 ( meso ‐ or rac ‐dpmppm) 4 L 2 ] 4+ (L = none, MeCN, N , N ‐dimethylformamide (dmf), and isocyanides),, which dissociate at higher temperature T > 100 °C into two tetrapalladium units of {Pd 4 ( meso ‐ or rac ‐dpmppm) 2 } 2+ and interestingly they are self‐aligned at lower temperature T < 60 °C to restore the original rods through asymmetric recognition between the tetrapalladium units . Two meso ‐ or rac ‐dpmppm ligands also assembled four Au I ions in syn ‐ and anti ‐arrangements with respect to the Au I 4 strings to form bent, linear, and zigzag Au 4 chains, which are strongly luminous from triplet states of multinuclear Au I centers and were sensitively quenched by capturing Cl – ions into their bent pockets , .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of developing low‐valent “extended metal atom chains (EMACs)”, we have studied transition‐metal complexes supported by linear tri‐ and tetraphosphine ligands, bis(diphenylphosphinomethyl)phenylphosphine (dpmp) and meso ‐ and rac ‐bis[(diphenylphosphinomethyl)phenylphosphanyl]methane (dpmppm), which are intended to be utilized as linearly incremental metal building blocks . During our studies, linear trinuclear complexes, [Pt 2 M(µ‐dpmp) 2 (XylNC) 2 ](PF 6 ) 2 {M = Pt ( 1a ), Pd ( 1b ); Xyl = 2,6‐xylyl}, were synthesized (Scheme ) and have proven to be good building blocks for further extended metal strings .…”
Section: Introductionmentioning
confidence: 99%